2010
DOI: 10.1051/0004-6361/200913946
|View full text |Cite
|
Sign up to set email alerts
|

On the physical properties ofz6–8 galaxies

Abstract: Aims. We analyse the spectral energy distributions (SEDs) of the most distant galaxies discovered with the Hubble Space telescope and from the COSMOS survey and determine their physical properties, such as stellar age and mass, dust attenuation, and star-formation rate. Methods. We use our SED fitting tool including the effects of nebular emission to analyse three samples of z ∼ 6−8 galaxies with observed magnitudes J AB ∼ 23 to 29. Our models cover a wide parameter space. Results. We find that the physical pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
221
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(256 citation statements)
references
References 75 publications
34
221
1
Order By: Relevance
“…We then computed the SFR from the Kennicutt (1998) relationship between UV luminosity and SFR. Our candidates have an SFR ≤ 25 M /yr, which is consistent with previous results (Labbé et al 2010, Schaerer & de Barros 2010.…”
Section: Star Formation Rate and Sizesupporting
confidence: 93%
See 1 more Smart Citation
“…We then computed the SFR from the Kennicutt (1998) relationship between UV luminosity and SFR. Our candidates have an SFR ≤ 25 M /yr, which is consistent with previous results (Labbé et al 2010, Schaerer & de Barros 2010.…”
Section: Star Formation Rate and Sizesupporting
confidence: 93%
“…For all of the objects in our sample, the best-fit SED is found at very high-redshift (z > 8.0) with a small 1σ confidence interval (dz < 1), meaning a good estimation of the photo-z. For most of the objects, the best-fit SED is found to have negligible dust content (A v = 0), as expected for very high-redshift objects (e.g., Schaerer & de Barros 2010). We also inspected the redshift probability distribution, P(z) to evaluate the probability that they are low-z interlopers.…”
Section: Sed-fittingmentioning
confidence: 84%
“…21 Nebular continuum emission could be an important component for very young (∼10 Myr) starbursts and can contribute up to ∼1/3 of the total continuum just blueward of the rest-frame 4000 Å break. Nebular continuum emission also makes the rest-frame UV slope redder than expected from stars alone (Schaerer & De Barros 2010).…”
Section: Modeling Proceduresmentioning
confidence: 99%
“…Recent studies have shown that for some galaxy candidates, strong nebular emission lines contribute significantly to broadband fluxes and therefore influence the inferred galaxy properties (e.g., Schaerer & De Barros 2010;Smit et al 2014). Therefore, we use galaxy templates that include nebular emission lines in the modeling.…”
Section: Modeling Proceduresmentioning
confidence: 99%
“…Recent studies have given the first estimates of masses, ages, and SFRs for single z > ∼ 6.5 objects, the first constraints on the stellar mass density at these epochs, and have also raised an interesting debate about the possibilty that the first galaxes might be characterized by peculiar properties, like a very low dust content, nearly primordial metallicity or top-heavy stellar initial mass functions (Finkelstein et al 2010;Bouwens et al 2010a;González et al 2010;Salvaterra et al 2010;Schaerer & de Barros 2010).…”
Section: Introductionmentioning
confidence: 99%